HOUSE OF EDUCATION OF THE BUKHARA PEOPLE'S SOVIET REPUBLIC IN MOSCOW - Nuridinov Turdali Qambarovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article highlights the creation and activities of the Bukhara House of Education in the city of Moscow.